Automatic parking system ( APS ) - Abusharkh, Suha; Alnajjar, Musab; Al-Daraweesh, Mohammad (جامعة بوليتكنك فلسطين - اتصالات, 2015)
people everywhere . and increasing the need of more parks , and more time is needed to find a place for a car to park. Our project proposes a solution to decrease the effect of this problem in our society . the idea of our project is to design an automatic parking system (APS) for drivers to reserve the suitable park slot for their cars before they arrive, which saves time , money and effort. Our system is based on sensors to detect the available slot, arduino to manage park slots, gates , and a zigbee network to connect with a server. The server is connected with a modem to communicate with mobile devices and billing service.
no of pages 80, 28848, اتصالات 2/2015 , in the store
Keywords: Automatic parking systems